DINAMIKA DAN PARADIGAMA STUDI AL-QURAN: Kontekstualisasi Penafsiran Ibn Kathîr dan Fazlurrahman - Wely Dozan (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
This paper tries to discuss the new direction of the development of Quran studies in the discourse of classical and contemporary interpretations. Specifically, this paper explores the thoughts of Ibn Kathir and Fazlur Rahman as a comparative study to see the development of the Quran’s interpretation methodology. It can be said that, Ibn Kathir's interpretation in understanding the Quran is textual. While, the development of Quran in the contemporary era in relation to Fazlur Rahman's thinking tends to be contextual. There are several new methodologies offered by Fazlurrahman in understanding texts, including: first, looking at the context of asbab al-nuzul verses; second, the approach (double movement); and third, the logical synthesis approach. This research employed a literature study approach to find related discussions through books, journals, and articles that were relevant to see the problems. The conclusion shows that Q.S. An-Nisa' 4: 3 according to Ibn Kathir is a text of polygamy, while according to Fazlur Rahman, it is not seen as a command to practice polygamy but monogamy in the context of marriage.